THE GENESIS OF THE SOURCES OF UKRAINIAN LAW IN THE CONTEXTOF THE EVOLUTIONARY STAGES OF LEGAL MODERNIZATION IN UKRAINE - КАРПІЧКОВ, Віталій; МІРОШНИЧЕНКО, Марія (Київський національний університет імені Тараса Шевченка, 2026)
B a c k g r o u n d . The current issue of the peculiarities of the evolution and development of the sources of Ukrainian law at each stage of its development, in the context of legal modernization in Ukraine, is addressed. M e t h o d s . The guiding concept in the scientific analysis was chosen as the concept of synthesis of Ukrainian history by Mykhailo Hrushevsky using the methods of system-information, socio-cultural and systemic approaches, which provided a comprehensive approach to modelling the genesis of the sources of Ukrainian law, taking into account the peculiarities of legal modernization in Ukraine in a historical perspective according to the formula "past-present-future". R e s u l t s . The model of the stages of evolution and development of Ukrainian law presented by the authors has several advantages over the variants of this process established in the scientific and educational literature. It allows, first, to “fit” the historical process of the development of Ukrainian law and its sources into the context of world history, while preserving its inherent specificity and multi-vector nature. At the same time, the peculiarities of the legal dynamics of both Western European countries and those imperial structures of which the lands of Ukraine were a part are taken into account; second, to observe continuity between stages. It is emphasized that the stage-by-stage nature ensures the continuity of the evolutionary process of Ukrainian law against the background of social, cultural development and legal life in the territories of Ukraine. C o n c l u s i o n s . Based on the research, the criterion for dividing into stages of the genesis of Ukrainian law was determined and trends in updating its sources at the current stage of legal modernization in Ukraine were formulated. It was established that when studying the features of the modernization of law and the genesis of its sources within the framework of each of the stages against the background of the general, historical process of legal modernization in Ukraine, attention should be focused on the entire spectrum of the socio-economic and spiritual life of the Ukrainian people. It has been determined that the main trends in the development of Ukrainian law and the renewal of its sources in conditions favourable for the development of national statehood and the national legal system are the actualization of the normative contract and legal custom as sources of law. Legal custom was and remains the ideal basis for the structure of national law, the analysis of which helps to realize the ontological meanings that structure the reality of legal life.

В с т у п . Порушено актуальну проблему особливостей еволюції та розвитку джерел українського права на кожному з етапів його розвитку в контексті правової модернізації в Україні. М е т о д и . Керівною в науковому аналізі обрано концепцію синтезу української історії Михайла Грушевського з використанням системно-інформаційного, соціокультурного і системного підходів, які забезпечили комплексний підхід до моделювання ґенези джерел українського права з урахуванням особливостей правової модернізації в Україні в історичній перспективі за формулою "минуле – сучасне – майбутнє". Р е з у л ь т а т и . Представлена авторами модель етапів еволюції та розвитку українського права має кілька переваг з усталеними в науковій і навчальній літературі варіантами цього процесу. Підкреслено, що етапність забезпечує неперервність еволюційного процесу українського права на тлі суспільного, культурного розвитку та правового життя на теренах України. Наголошено, що в процесі аналізу особливостей еволюції та розвитку джерел українського права на кожному з етапів його історії слід концентрувати увагу, по-перше, на самоорганізаційних аспектах правового життя українського народу, присутності чи відсутності юридичних умов свободи особистості; по-друге, спостерігати спадкоємність між етапами. В и с н о в к и . На основі проведеного дослідження визначено критерій поділу на етапи ґенези українського права та сформульовано тенденції в оновленні його джерел на сучасному етапі правової модернізації в Україні. Установлено, що, досліджуючи особливості модернізації права та ґенезис його джерел у межах кожного з етапів на тлі загального, історичного процесу правової модернізації в Україні, слід зосереджувати увагу на всьому спектрі соціально-економічного й духовного життя українського народу. Визначено, що основними тенденціями в розвитку українського права й оновленні його джерел в умовах, сприятливих для розбудови національної державності та національної правової системи, є актуалізація нормативного договору і правового звичаю як джерел права.
ҐЕНЕЗИС ДЖЕРЕЛ УКРАЇНСЬКОГО ПРАВАВ КОНТЕКСТІ ЗАГАЛЬНОЇ ХАРАКТЕРИСТИКИ ЕТАПІВ ЙОГО ЕВОЛЮЦІЇВ УМОВАХ ПРАВОВОЇ МОДЕРНІЗАЦІЇ В УКРАЇНІ
Keywords: державотворення в Україні; види джерел права; історичний синтез; модернізація законодавства; правова модернізація; правова система; українське право; еволюція українського права; правовий менталітет; state formation in Ukraine; sources of law; types of sources of law; historical synthesis; modernization of legislation; legal modernization; legal system; Ukrainian law; evolution of Ukrainian law; legal mentality